2015
DOI: 10.1016/j.hrthm.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous nerve activity and spontaneous ventricular arrhythmias in ambulatory dogs

Abstract: Background Stellate ganglion nerve activity (SGNA) is important in ventricular arrhythmogenesis. However, because thoracotomy is needed to access the stellate ganglion, it is difficult to use SGNA for risk stratification. Objective To test the hypothesis that subcutaneous nerve activity (SCNA) in canines can be used to estimate SGNA and predict ventricular arrhythmia. Methods We implanted radio transmitters to continuously monitor left stellate ganglion and subcutaneous electrical activities in 7 ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…SGB, by mitigating catecholamine release, likely reverses the findings in a canine post-infarct model of shortened ERP in abnormal ventricular myocardium, and increased inducibility of arrhythmias in the presence of catecholamines (41). SGB may also be particularly useful for attenuating burst discharge activity in left stellate ganglion, which has been shown to precede most VT and sudden cardiac death in a canine model of ischemic cardiomyopathy (4243). Sympathoexcitation increases repolarization heterogeneity (4446), increases risk of delayed after depolarizations (47,48), and increases arrhythmia inducibility (49).…”
Section: Discussionmentioning
confidence: 99%
“…SGB, by mitigating catecholamine release, likely reverses the findings in a canine post-infarct model of shortened ERP in abnormal ventricular myocardium, and increased inducibility of arrhythmias in the presence of catecholamines (41). SGB may also be particularly useful for attenuating burst discharge activity in left stellate ganglion, which has been shown to precede most VT and sudden cardiac death in a canine model of ischemic cardiomyopathy (4243). Sympathoexcitation increases repolarization heterogeneity (4446), increases risk of delayed after depolarizations (47,48), and increases arrhythmia inducibility (49).…”
Section: Discussionmentioning
confidence: 99%
“…8 However, Doytchinova et al recently demonstrated that SCNA can be used as a surrogate for SGNA to predict susceptibility to ventricular tachyarrhythmias in a canine model with sudden cardiac death. 7 …”
Section: Discussionmentioning
confidence: 99%
“…6 Subcutaneous inter-electrode distance was not measured at the time of the study, but in similar sized dogs it is estimated at around 28 cm. 7 After baseline recording, acute MI was created and recording continued for an additional 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of sympathetic hyperactivity outside the heart in arrhythmogenesis has also been reported by Huang et al [30] that electrical stimulation of the left renal sympathetic nerves induced both systemic and cardiac sympathetic hyperactivity and increases the incidence of ischemia-induced VT/VF. In another study, continuous recording of the LSG activity in ambulatory dogs after myocardial infarction (MI) demonstrated that increased LSG and subcutaneous nerve activity preceded the episodes of premature ventricular contractions and VT/VF [31] .These studies strongly indicate that sympathetic hyperactivity and heterogeneous sympathetic nerve sprouting or hyperinnervation are tightly associated with the occurrence of VT/VF.…”
Section: Ventricular Tachycardia and Fibrillation (Vt/vf)mentioning
confidence: 96%